Constitutions and the Political Agency of Women: A Cross-Country Study - Austen, Siobhan; Mavisakalyan, Astghik (Taylor & Francis, 2016)
The underrepresentation of women in parliaments worldwide warrants attention to discern underlying sources. This study examines one potential source: the countries’ constitutions. Based on a large cross-country dataset from 2011, the study demonstrates that women's representation in parliament is larger in countries with constitutional protection from gender-based discrimination. Baseline estimates suggest that the presence of such protection results in over a 3.5 percentage point increase in women's share of parliamentary seats. The study probes some underlying mechanisms and shows that places with constitutional protection from gender-based discrimination are likely to have legislation directly targeting women's underrepresentation. The results underscore the role of constitutional design in promoting women's political agency.